Assessment of statistical and hybrid LES turbulence closures for surface combatant DTMB5415 at 20° static drift condition - Visonneau, Michel; Guilmineau, Emmanuel; Wackers, Jeroen; Deng, Ganbo; Queutey, Patrick (Volume 11: Prof. Robert F. Beck Honoring Symposium on Marine Hydrodynamics, 2015)
International audience This paper provides detailed validation of the complex free-surface flow around the surface combatant DTMB5415 at 20 • static drift conditions. Particular emphasis is being placed on the onset and progression of the various vortical structures created at the sonar dome, at the free-surface and around bilge keels in conditions where free-surface breaking may occur. A detailed analysis of this complex free-surface flow is conducted on grids which are dynamically refined to capture the vortical structures. Local comparisons with recent experiments performed at the Iowa Institute of Hydraulic Research (IIHR) during a joint NATO-AVT (Advanced Vehicle Technologies) collaboration are used to perform detailed flow analysis and draw some conclusions about the actual potentialities of advanced Computation Fluid Dynamics (CFD) method in terms of physical and numerical modeling.